Comparative Efficacy of the Conventional and Experimentally Developed Duck Plague Vaccine - Hossain, M.T.; Islam, M.A.; Amin, M.M.; Islam, M.A. (International Journal of Poultry Science, 2005)
The comparative efficacy between the conventional vaccine (DLS-DPV) and experimentally prepared duck plague vaccine (BAU-DPV) was evaluated in seventy-five 35-day-old Zinding breed ducklings during the period from October/02 to March/03. The ducklings were equally divided into five groups (A, B, C, D and E). Ducklings of group A and B were primarily vaccinated with 0.5 ml and 1.0 ml of DLS-DPV respectively and those of group C and D were primarily vaccinated with 0.5 ml and 1.0 ml of BAU-DPV. The ducklings of group E were kept as unvaccinated control. Five months after primary vaccination all the ducks of vaccinated groups were boosted with 1.0 ml of DLS-DPV and BAU-DPV and 21 days after booster vaccination all the ducks of vaccinated and control groups were challenged with 1ml of 10 4 EID50 of virulent field isolate of duck plague virus (DPV). The level of immunity developed in different vaccinated groups of ducks was measured by passive hemagglutination (PHA) test. The mean PHA titre of birds of group A, B, C and D after primary vaccination were 38.4 ± 6.4, 28.8 ± 3.2, 51.2 ± 7.84 and 38.4 ± 6.4 and after booster vaccination were 153.6 ± 25.6, 76.8 ± 12.8, 358.4 ± 62.71 and 115.2 ± 12.8 respectively. Results of PHA test indicated that experimentally prepared duck plague (BAU-DPV) vaccine revealed higher immune response compared to that of the conventional (DLS-DPV) vaccine and results of the challenge experiment indicated that the mean PHA titre over 100 after booster vaccination revealed 100% protection.